Neonatal diabetes mellitus: current perspective - Kataria A; Palliyil Gopi R; Mally P; Shah B (Research and Reports in Neonatology, 2014)
Anglina Kataria,1 Resmy Palliyil Gopi,2 Pradeep Mally,3 Bina Shah21Department of Pediatrics, 2Pediatric Endocrinology, Department of Pediatrics, 3Neonatology, Department of Pediatrics, NYU School of Medicine, New York, NY, USAAbstract: Neonatal diabetes mellitus (NDM) is a rare form of diabetes characterized by hyperglycemia occurring in the first few months of life. It can present as either transient NDM (TNDM), which resolves by a few months, or permanent NDM (PNDM), which continues throughout life. The etiology of this disease remained unclear until recently, when advances in molecular genetic techniques illuminated the mechanisms involved in the pathogenesis of the disease. Having delineated the genes involved in insulin production and secretion and their association with NDM, we currently understand the molecular basis of this disease. While most TNDM cases are caused by the overexpression of chromosome 6q24, the majority of PNDM cases are due to mutations in the adenosine triphosphate-sensitive potassium (KATP) channel. The improved understanding of the etiology of the disease had revolutionized the diagnosis and its management with oral sulfonylureas. The primary objective of this study was to review the current understanding of neonatal diabetes, including its genetic etiologies, clinical presentation, diagnosis, acute treatment, and long-term management.Keywords: hyperglycemia, intrauterine growth retardation, KATP channel mutations, sulfonylurea